Experiments with embedded system design at UMinho and AIT - Tavares, Adriano (2012)
Nowadays, embedded systems are central to modern life, mainly due to the scientiﬁc and technological advances of the last decades that started a new reality in which the embedded systems market has been growing steadily, along with a monthly or even weekly emergence of new products with diﬀerent applications across several domains. This embedded system ubiquity was the drive for the following question ”Why should we focus on embedded systems design?” that was answered in [1, 2] with the following points: (1) high and fast penetration in products and services due to the integration of networking, operating system and database capabilities, (2) very strategic ﬁeld economically and (3) a new and relatively undeﬁned subject in academic environment. Other adja- cent questions have been raised such as ”Why is the design of embedded systems special?”. The answer for this last question is based mainly on several problems raised by the new technologies, such as the need for more human resources in specialized areas and high learning curve for system designers. As pointed in [1], these problems can prevent many companies from adopting these new technologies or force them not to respond timely in mastering these technological and market challenges. In this paper, it is described how staﬀ at ESRG-UMinho 1 and ISE-AIT 2 faced the embedded systems challenges at several levels. It starts to de- scribe the development of the educational context for the new technolo- gies and show how our Integrated Master Curriculum in Industrial Elec- tronics and Computer Engineering has been adapted to satisfy the needs of the major university customers, the industry.